Association of HLA-DR2-Related Haplotype (HLA-DRB5*01-DRB1*1501-DQB1*0602) in Patients with Multiple Sclerosis in Khuzestan Province - Delfan, Nooshin; Galedari, Hamid; Ghanbari Mardasi, Farideh; Zabihi, Rezvan; latifia, Tahereh; Tahereh Seifi; Madjdinasab , Nastaran (Iranian Journal of Child Neurology, 2021)
Abstract Objective Multiple sclerosis is a partially heritable autoimmune disease. HLA-DR2 is the largest identified genetic risk factor for MS. The largest identified genetic risk factor is haplotype from the MHC class II HLA-DR2 which increases risk of disease. The HLA-DR2 distribution in MS patients has been confirmed but contradictory outcomes have been found although its effect on ethnicity and gender is unclear. Since, there are no data regard to the association of HLA-DR2 (HLA-DRB1*1501-DRB5*01-DQB1*0602) with MS in Khuzestan, and because of ethnic diversity, investigating the association of HLA-DR2 with MS disability in both sex and ethnicity, was the aim of this study. Materials & Methods A total of 399 individuals were recruited in the study. HLA typing was conducted using the polymerase chain reaction amplification with sequence-specific primers (PCR-SSP) technology. Moreover, HLA-DR2 association with MS was analyzed. Also, probable association with gender, ethnicity, EDSS, MS clinical course was examined by chi square test. Results HLA-DRB5*01--DQB1*0602- as the most common HLA haplotype was found in both patient and control groups. In contrast, DRB5*01+-DRB1*1501+-DQB1*0602- frequency was very low. It was observed that no haplotype has association with MS susceptibility. Interestingly, none of the haplotypes showed association with ethnicity, sex, EDSS and MS course except for HLA-DRB5*01+-DRB1*1501+-DQB1*0602- haplotype that was positively associated with EDSS steps 5 to 10 (p=0.014) and non-RRMS (p = 0.023). Conclusion There was no association between HLA-DR2 and MS susceptibility. However, the higher HLA-DRB5*01+-DRB1*1501+-DQB1*0602- frequency may play a role in MS development. Also, HLA-DR2 did not increase significantly concerning clinical course, ethnicity, sex, and EDSS. This study further supports the importance of replication studies as susceptible loci that might differ in various ethnicities. Therefore, it is concluded that the association between HLA-DR2 and MS is more allelic than haplotypic in Khuzestan